URGENSI PEMAHAMAN ASAL-USUL KATA BAHASA HUKUM DALAM PENERJEMAHAN DAN TRANSLITERASI TERMINOLOGI HUKUM - Nugroho, Agus Digdo Nugroho; Johanes, Johanes (Jurnal Penerjemahan, 2024)
The activity of translating legal documents has unique precision and characteristics where the translator must also be observant in seeing the origins of the terminology used. Each legal terminology has effective application according to the legal system where it originates and will be used in the target language which adheres to what kind of legal system. In general, the legal system in the world is dominated by the Continental European and Anglo Saxon systems, although there are also other legal systems. Likewise, regarding transliteration activities of characters containing legal language. In this journal article the author will explain the forms of bias in selecting inappropriate diction in translation activities. The method used is a qualitative method with data in electronic media. From the results of this research, it was found that there is a bias in the use of inappropriate legal terminology and mixed usage. Some translators ignore and are not sensitive that legal terminology has a different context in which it applies even though it has close meanings. This also happens in transliteration activities where there are still many writing errors where translators collide Arabic-Latin transliteration guidelines with foreign loanwords which have officially become Indonesian.